TO THE QUESTION OF THE ROLE OF FREE FATTY ACIDS IN THE FORMATION OF INSULIN RESISTANCE AND METABOLIC SYNDROME - Nelli Uzbekova Rafikovna (Scholar Express Journals, 2022)
This article provides information on obesity as one of the leading causes of metabolic syndrome (MS), insulin resistance (IR), type 2 diabetes (DM2) and consequent cardiovascular disease (CVD).
Keywords: Obesity; Metabolic Syndrome; Insulin Resistance; Diabetes Mellitus; High Economic Situation